2013
DOI: 10.1002/adhm.201300189
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Accumulation of Sub‐2 nm Gold Nanoclusters for Cancer Radiation Therapy

Abstract: A new type of metabolizable and efficient radiosensitizers for cancer radiotherapy is presented by combining ultrasmall Au nanoclusters (NCs, <2 nm) with biocompatible coating ligands (glutathione, GSH). The new nanoconstruct (GSH-coated Au25 NCs) inherits attractive features of both the Au core (strong radiosensitizing effect) and GSH shell (good biocompatibility). It can preferentially accumulate in tumor via the improved EPR effect, which leads to strong enhancement for cancer radiotherapy. After the treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
194
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 329 publications
(197 citation statements)
references
References 43 publications
3
194
0
Order By: Relevance
“…Those metal NCs, mainly gold, are made of ten to hundred atoms and usually presented as species filling the gap between molecules and nanoparticles. [1][2][3][4] Gold nanoclusters (Au NCs) present several features making them appealing for cancer therapy thanks to (i) their high renal clearance 5,6 reducing toxicity risk, (ii) the relatively high tumor retention by passive uptake, 7,8 (iii) the ability to trigger cell death under light illumination 9 or radiosensitization, [10][11][12] and (iv) the detection by multimodal imaging techniques. [13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Those metal NCs, mainly gold, are made of ten to hundred atoms and usually presented as species filling the gap between molecules and nanoparticles. [1][2][3][4] Gold nanoclusters (Au NCs) present several features making them appealing for cancer therapy thanks to (i) their high renal clearance 5,6 reducing toxicity risk, (ii) the relatively high tumor retention by passive uptake, 7,8 (iii) the ability to trigger cell death under light illumination 9 or radiosensitization, [10][11][12] and (iv) the detection by multimodal imaging techniques. [13][14][15] In optical imaging, one of the great advantages of Au NCs compared to plasmonic Au nanoparticles (Au NPs) is related to the ability to visualize them by fluorescence in the red-near-infrared (NIR) region (650-800 nm), a spectral window suitable for in vivo studies due to the reduced tissue scattering and low blood absorption.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…[1][2][3] Unlike traditional large size nanoparticles (NPs, .10 nm), [4][5][6] typical Au NCs have a renal clearance cutoff of less than 5.5 nm, 7 to easily escape the reticuloendothelial system (RES) and accumulate in the tumor tissue. 3,8,9 Therefore, they are widely applied in imaging, drug deliveries, and cancer radiation therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies in mice have demonstrated the rapid and efficient clearance of glutathione stabilised-Au NCs due to their size being smaller than the kidney filtration threshold (∅∼5.5nm) [49][50] . NCs have shown also promising results for cancer therapy 49,51 and vaccine development 52 . For example, we have recently shown how their small size and the use of a zwitterionic ligand promotes their uptake by monocyte-derived DCs and induces a strong immunosuppressive effect 52 , which we believe to be related to the dual action of the high diffusion of the particle in solution and the ligand contribution.…”
Section: Introductionmentioning
confidence: 99%